Industry and Regulatory Performance in 2012: A Year in Review. Issue 3 (8th May 2013) - Dowden, H M; Jahn, R; Catka, T; Jonsson, A; Michael, E; Miwa, Y; Zinkand, W
<x xml:space="preserve">Abstract</x> 2012 was a robust year for new molecular entity (NME) approvals in the major geographic regions. What is behind this apparent improved performance? Has the pharmaceutical industry turned the tide in research and development productivity? In this analysis, we look not only at the number of approvals in 2012 but also at their clinical and market potential. We discuss how changes in the regulatory and reimbursement environment impact current industry performance and how this might evolve. Clinical Pharmacology & Therapeutics (2013); 94 3, 359–366. doi:10.1038/clpt.2013.91